2016
DOI: 10.1126/sciadv.1600477
|View full text |Cite
|
Sign up to set email alerts
|

Tunable room-temperature spin-selective optical Stark effect in solution-processed layered halide perovskites

Abstract: A new spin on perovskites untwined: Ultrafast optical switching and tuning of spin-energy states in layered halide perovskites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
184
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(195 citation statements)
references
References 37 publications
9
184
2
Order By: Relevance
“…45,46 The organic component does not play a signicant role in determining the electronic structure. 41,47 The optical transitions in 2D perovskites thus stem from the 6s to 6p transition in Pb 2+ , which is similar to that in PbI 2 . Because Pb(207) has a larger atomic mass than I(126), the Pb atoms undergo Bose-Einstein oscillation at a low frequency that induces acoustic phonons, whereas the I atoms predominantly exhibit high-frequency Bose-Einstein oscillations, resulting in optical phonons.…”
Section: Resultsmentioning
confidence: 78%
“…45,46 The organic component does not play a signicant role in determining the electronic structure. 41,47 The optical transitions in 2D perovskites thus stem from the 6s to 6p transition in Pb 2+ , which is similar to that in PbI 2 . Because Pb(207) has a larger atomic mass than I(126), the Pb atoms undergo Bose-Einstein oscillation at a low frequency that induces acoustic phonons, whereas the I atoms predominantly exhibit high-frequency Bose-Einstein oscillations, resulting in optical phonons.…”
Section: Resultsmentioning
confidence: 78%
“…When a semiconducting system is excited by a laser pulse with photon energy lower than that of exciton transition, a virtual optical transition is invoked resulting in so-called photon-dressed states12345678910111213141516. It usually interacts repulsively with original states, leading to the characteristic blue-shift of the exciton energy spectrum.…”
mentioning
confidence: 99%
“…It usually interacts repulsively with original states, leading to the characteristic blue-shift of the exciton energy spectrum. Along with the fact that the coherent interaction can only take place during the time duration of an ultra-short laser pulse, such a unique feature makes this phenomena, the so-called excitonic optical Stark effect, ideal for ultrafast optical switches and modulators34567891012131415161718. So far, however, there has been no strategy for energy-selective control of exciton states.…”
mentioning
confidence: 99%
“…Figure g shows the results obtained under co‐ and counter‐circularly polarized light conditions, which are consistent with the preceding discussion. In the same year, Giovanni et al also observed a strong Stark effect in HOPs . Circularly polarized pulses were used to select the spin states, tuning them by ≈6.3 meV, which provides the same effect as application of magnetic fields as large as 70 T. They also studied different kinds of 2D perovskite thin films that were processed using low‐temperature solutions.…”
Section: Novel Spin‐related Physical Effects Arising From Hopsmentioning
confidence: 99%
“…A magnetic field B z is set vertical to the injected laser to measure the Hanle effect. a,b) Reproduced with permission . Copyright 2016, American Association for the Advancement of Science.…”
Section: Novel Spin‐related Physical Effects Arising From Hopsmentioning
confidence: 99%